2022
DOI: 10.1177/02666669221136864
|View full text |Cite
|
Sign up to set email alerts
|

Workplace creativity and job satisfaction of academic librarians: A perspective of distributed leadership theory

Abstract: Distributed leadership (DL) is a less focused area in librarianship and further limited literature in the context of workplace creativity and job satisfaction. This study investigates the impact of DL dimensions (decision making, delegation of authority, and motivation) on workplace creativity and job satisfaction in the academic libraries of Pakistan. A quantitative research approach was used and data was collected through an adapted questionnaire. A purposive sampling method was used, and the data was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…Analysis of the impact of leadership on the performance of employees through motivation and achievement of job satisfaction has been presented in many studies (Semedo et al, 2022, Elifneh and Daniel, 2022, Nguyen et al, 2022, Zarei and Issahaka, 2022, Gao et al, 2022, Dash et al, 2022, Ashiq et al, 2023. Leaders are interested in attracting and retaining highly skilled and experienced employees to perform tasks aimed at achieving the strategic objectives and tactical objectives of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the impact of leadership on the performance of employees through motivation and achievement of job satisfaction has been presented in many studies (Semedo et al, 2022, Elifneh and Daniel, 2022, Nguyen et al, 2022, Zarei and Issahaka, 2022, Gao et al, 2022, Dash et al, 2022, Ashiq et al, 2023. Leaders are interested in attracting and retaining highly skilled and experienced employees to perform tasks aimed at achieving the strategic objectives and tactical objectives of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Distributed leadership supports personnel to collaborate and bring ideas and expertise together so that their collective action achieves more than their individual actions and serves as a catalyst for library service development and innovation (Goulding & Walton, 2014). Ashiq et al (2022) observed that Distributed leadership is a less-focused area in Librarianship. But some scholars such as Jeenn (2022) and Johnston (2015) have argued that Distributed leadership was propounded to erase the belief that leadership is often held in one person.…”
Section: Managers or Leaders In 21st Century Libraries: Justifying Th...mentioning
confidence: 99%
“…Distributed Leadership supports library personnel to collaborate and bring ideas and expertise together so that their collective action achieves more than their individual actions and serves as a catalyst for library service development and innovation (Goulding and Walton, 2014). Ashiq et al (2022) observed that Distributed Leadership is a less focused area in Librarianship. But some scholars such as Jenn (2022) and Johnston (2015) have argued that Distributed Leadership was propounded to erase the belief that leadership is often held in one person.…”
Section: Introductionmentioning
confidence: 99%
“…Ashiq et al (2022) observed that Distributed Leadership is a less focused area in Librarianship. But some scholars such as Jenn (2022) and Johnston (2015) have argued that Distributed Leadership was propounded to erase the belief that leadership is often held in one person.…”
Section: Introductionmentioning
confidence: 99%